The profile of patients with idiopathic Parkinson's Disease in a South African hospital complex: an institution-based observational study - Smith, Marcelle (My University, 2017)
Idiopathic Parkinsons Disease (IPD) has not been well studied in Black African populations. Data on the demographics, phenotype differences with Caucasoid populations, severity and frequencies of IPD in Black Africans is scant. Aim: to determine the impact of ethnicity and gender on the phenotype of IPD in South African patients. Method: Fifty patients with diagnosed IPD were recruited. The data collection was in the form of a questionnaire and clinical evaluation which included a mental status examination (MMSE), and illness staging. Results: Thirty-five patients were Black African, eleven were white European descendant, three were of Indian descent and one had mixed ancestry. Twenty-eight of the patients were female. There were no significant gender differences within or between the different ethnic groups. Seventy- one percent of black and ninety-one percent of white participants had classic IPD presentations. A resting tremor was found in fifty-nine percent of all males in the study but in ninety-four percent of females. In the black IPD patients, thirty-one percent had 7 early onset IPD (age of onset less than 50 years) with a gender ratio of M:F=1:6. Twenty-nine percent had an akinetic-rigid syndrome with erect posture and no tremor (gender ratio of M:F = 7:4) and seventy-four had cognitive impairment (gender ratio of M:F =8:5). Conclusion: The phenotype of IPD in the majority of our study population is of the classic IPD type. In a third of our Black patients the onset was early and in a third the presentation was akinetic. Keywords: Parkinsons disease; Gender; Ethnicity
A research report submitted to the University of the Witwatersrand for the purpose of the degree of Master of Medicine, Neurology, March 2017
Keywords: Ethnicity and Gender - Phenotype of Parkinsons Disease; Parkinson Disease